Maximizing Mentorship Relationships: Leveraging Intersubjective Theory for Productive Interactions - Adeoye, Moses Adeleke (Indonesian Values and Character Education Journal, 2024)
Mentorship is a dynamic and transformative relationship where an experienced individual, known as the mentor, gives guidance, assistance, and expertise to a much less experienced individual, called the mentee, to assist them in broadening their view and professionally. This study explores the application of the intersubjective theory in maximizing mentorship relationships for extra-effective interactions. Intersubjectivity theory emphasizes the importance of understanding the subjective views and perspectives of each mentor and mentee to cultivate greater significant and powerful mentorship dynamics. By delving into the nuances of intersubjective communication and understanding, this research aims to offer insights and techniques that can be used to boost mentorship studies and results. Through an aggregate of theoretical evaluation and realistic implications, this study offers a new perspective on how intersubjective ideas can be leveraged to optimize mentorship interactions in diverse professional and academic settings. In conclusion, the integration of intersubjective concepts into mentorship practices can revolutionize the manner we method mentoring relationships, transferring the point of interest from hierarchical and directive models closer to greater collaborative and egalitarian frameworks. By embracing the standards of intersubjectivity, mentors can foster a lifestyle of shared knowledge and empowerment, wherein both mentors and mentees are valued as equal partners in the pursuit of private and professional development.